Range Optimization Using Trajectory Shaping Analysis Of A Surface-Launched Rocket - Saeedipour, Hamid Reza; Mohd Yusof, lIIyia (2004)
This paper is outlined the design and flight performance ot an advanced Surface-Launched Rocket. Brief descriptions of the technologies in the rocket design, parameters driving the rocket design & performance, the rocket performance prediction and examples of maximizing flight performance are presented.